Struktur Komunitas Echinodermata pada Berbagai Tipe Habitat di Daerah Intertidal Pantai Lakeba, Kota Baubau Sulawesi Tenggara - WD. Syarni Tala; Kusrini Kusrini; Jumiati Jumiati (Jurnal Kelautan Tropis, 2021)
Echinoderms are one of organisms that inhabit intertidal areas which have important ecological roles in marine ecosystems, also have high economic values. The community structure and distribution pattern of Echinoderms in the intertidal area can provide an overview of the condition of the Echinoderm community. This research aims to determine the community structure of Echinoderms in various habitat types in the intertidal areas of Lakeba Beach, Baubau Town. The community structure of Echinoderms were observed using quadratic transec method. Echinoderms found were 777 individuals consisting of 18 species from 5 classes. Echinoderms were distributed in four habitat types, i. e. sandy, sand covered with seagrass, rocky, and rock covered with algae habitats. The highest abundance of Echinoderm was Ophiocoma scolopendrina (Ophiuroidea) and the lowest were Maretia planulata, Arachnoides placenta (Echinoidea), Holothuria scabra, H. leucospilota, Stichopus horrens (Holothuroidea), and Isocrinidae (Crinoidea). The species diversity of Echinoderms was categorized as moderate (H’ = 1,42180), species evenness was moderate (E = 0,49191), and no dominant species of Echinoderm community (D = 0,36601). Echinoderm community living in the intertidal area was influenced by antropogenic factors.  Echinodermata merupakan salah satu organisme yang mendiami daerah intertidal yang memiliki peran ekologis penting bagi ekosistem laut, juga memiliki nilai ekonomis yang tinggi. Struktur komunitas dan pola distribusi Echinodermata pada daerah intertidal dapat memberikan gambaran mengenai kondisi komunitas Echinodermata. Penelitian ini bertujuan untuk mengetahui struktur komunitas dan pola distribusi Echinodermata di daerah intertidal Pantai Lakeba, Kota Baubau. Struktur komunitas dan pola distribusi Echinodermata diamati menggunakan metode transek kuadrat. Echinodermata yang ditemukan berjumlah 777 individu yang terdiri atas 18 jenis dari 5 kelas. Echinodermata terdistribusi pada empat tipe habitat yaitu habitat pasir, pasir yang ditutupi lamun, batu, dan batu yang ditutupi alga. Echinodermata yang memiliki kelimpahan tertinggi adalah Ophiocoma scolopendrina (Ophiuroidea) dan kelimpahan terendah adalah Maretia planulata, Arachnoides placenta (Echinoidea), Holothuria scabra, H. leucospilota, Stichopus horrens (Holothuroidea), dan Isocrinidae (Crinoidea). Keanekaragaman jenis Echinodermata dikategorikan sedang (H’ = 1,42180), kemerataan jenis sedang (E = 0,49191) dan tidak ada jenis yang dominan dalam komunitas Echinodermata (D = 0,36601). Komunitas Echinodermata yang hidup di daerah intertidal pantai dipengaruhi oleh faktor antropogenik.